Tingkat Kualitas Permukiman (Studi Kasus: Permukiman Sekitar Tambang Galian C Kecamatan Weru Kabupaten Sukoharjo) - Lilik Anjar Setiawan; Winny Astuti; Erma Fitria Rini (Regional Development Information Center, Universitas Sebelas Maret, 2017)
Settlement is defined as a components combination of housing, environment and life of the societies who live in it. Quality of settlement components can describe how the condition of the settlement itself. Several settlement areas in Weru Subdistrict, Sukoharjo District have a C-type quarry location inside. Based on the Sukoharjo District Spatial Plan, that area is planned as settlement activities. There are other activities that should be supported by the components of the settlements that only planned to accommodate settlement activities. Question in this research is to know the level of settlement quality of each block in settlement area around C-type quarry in Weru Subdistrict seen from (1) nature, (2) shell, (3) infrastucture network, and (4) society. This research is a quantitative research using scoring analysis technique. The result shown that there is difference between each block of settlement. Block 2 has high quality because it has several components with high quality such as buildings, infrastructure network, and the level of public health. The other blocks such as block 1, block 3, block 4, and block 5 have medium quality with several medium quality of components such as green space, road network, economic level and level of public health. Improvement are needed for some components to improve the quality of settlements in each block so that the whole settlements becomes better to lived.